A new approach to the analysis of piezoelectric cladded acoustic fibers - Ucer, M; Akcakaya, E (Institute of Electrical and Electronics Engineers (IEEE), 1999)
In this paper, a new effective analysis method is proposed for the piezoelectric cladded acoustic fiber of hexagonal crystal symmetry. Interpreting all quantities appearing in the boundary conditions as state variables, a first-order differential equations system is obtained to investigate the waves in cladded acoustic fiber of hexagonal symmetry. This approach makes possible the analysis of cladded fibers by the general transmission-matrix technique. By using this method, dispersion relations for all modes are easily obtained. Examples of several materials are given. This method can also be applied in the analysis of the multilayered cylindrical fiber for which the individual layers have hexagonal symmetric piezoelectrical material.